Changes in dietary habits and weight status during the COVID-19 pandemic and its association with socioeconomic status among Iranians adults - Maharat, Maryam; Sajjadi, Seyedeh Forough; Moosavian, Seyedeh Parisa (Frontiers in Public Health, 2023)
Background: COVID-19 pandemic has impacted human health through sudden lifestyle changes, including isolation at home, and social distancing. Therefore the current study aimed to investigate the effect of the COVID-19 pandemic on eating habits, weight status, and their associations with socioeconomic status. Methods: This cross‑sectional study was conducted using an online structured questionnaire that inquired demographic, anthropometric (reported weight and height); dietary habits (weekly intake of certain foods); and dietary supplement intake information. Results: A total of 1187 participants completed the questionnaire, and after validation of the data, 1106 respondents were included in the study, with a mean age of 34.5±9.4 years. Our findings showed that the body mass index (BMI) of the participants significantly increased during COVID-19 (P<0.001). Also, there were significant changes in the intake of a variety of food and beverage during the COVID‑19, including less consumption of milk, yogurt, red meat, fish, canned fish, homemade fast foods, take out fast foods, carbonated drinks, and more consumption of whole bread, legumes (chickpeas, lentil, peas, kidney beans, black beans, pinto beans, and navy beans) , soy bean, nuts, seeds, high vitamin C vegetables, high vitamin C fruits, green-yellow fruits and vegetables, onion/garlic, dried fruits, natural fruit juices, and water (P<0.001; for all). It is informed that individuals consumed more vitamin and mineral supplements (P < 0.001). Also, before and during COVID‑19 pandemic weekly intakes of dairy, red meat, poultry, high vitamin C fruits, and whole bread were positively associated with socioeconomic status (P<0.001). Conclusion: Overall, this study indicates changes in body weight, dietary habits and supplement intake during the pandemic. Therefore, the findings of this study are valuable for, health professionals and politicians to better public health practice and policy making.